Analyzing the Stability and Safety of Artificial Slopes along the Alwadi Road in Sabratha City, Libya - Aboalgasem Alakhdar (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the stability of artificial slopes along the valley road in Sabratha, northwestern Libya, where quarrying activities have created unstable slopes from unconsolidated limestone debris lacking proper design. Laboratory tests measured cohesion and friction angles under varying moisture levels. Using RocPlane software, slope models were analyzed at two configurations: 40°/10 m and 20°/3 m. Results showed that increasing water content significantly reduces shear strength; at 80 mm water, the friction angle dropped to 30.9° and cohesion to 17.22 tons/m². Reducing the slope angle and height improved stability. Simulations revealed that poorly designed slopes with quarry waste have low safety factors and high collapse potential. The study underscores the need for proper engineering design to enhance slope stability and reduce geotechnical hazards.